A Reliable Architecture for IoT-based Aquatic Monitoring System of Coral Reef and Algae - Jemat A.; Sameon S.S.; Ghapar A.A.; Ramachandran T.; Nazeri S. (Penerbit Akademia Baru, 2024)
The coral reef population worldwide faces degradation issues due to various human-related factors such as pollution, overfishing, collecting live corals for the aquarium market, warm climate, thermal stress and ocean acidification. These factors lead to an imbalance in the natural ecosystem where the coral reef and algae reside. Coral reefs are susceptible to the changes in their natural ecosystem. This work aims to study the optimum condition for the coral reef and algae to healthy flourish. The main factors that influence the growth and survival of coral reefs and algae are also studied. Thus, this paper presents a proposed monitoring system-based IoT to monitor the coral reef and algae ecosystem. The system also intends to introduce a regulatory mechanism which can regulate the main factors identified to maintain an optimum condition for the coral and algae to prosper. In order to support the intention, a reliable network system and communication are needed to ensure that accurate information can be obtained. The system consists of sensors, microcontrollers, and a web application for monitoring real data of three different parameters most affected the ocean water: pH, temperature and salinity. 2023, Penerbit Akademia Baru. All rights reserved.